MANAJEMEN KURIKULUM TERPADU DI SEKOLAH ALAM BERCIRI KHAS ISLAM - Zoga Adipratama; Raden Bambang Sumarsono; Nurul Ulfatin (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2018)
Abstract: The purpose of this research is to find out about the implementation of school curriculum management nature. characteristic of Islam. This research uses qualitative descriptive method with this type of case studies. A data source includes the principal researchers, teachers, students and representatives of the principal part of the curriculum. Data collection techniques in the form of interviews, observation, documentation. Data analysis was conducted concurrently with data collection in the field with the analysis process consists of a reduction of data, display data, and verify the data. The results of this research are (1) planning curriculum through workshops to prepare learning devices for one academic year, (2) the preparation of the school calendar is done after receiving a calendar of national education, (3) preparing the progam work performed each end of the new school year and the school do the evaluation at the end of each year to determine the new work program next, (4) preparation of the schedule of lessons arranged by vice principal part of the curriculum and its curriculum with the team see the urgency subjects of competence which are then invited to the head of school, (5) the Division of the burden of teaching based on the number of teachers and the number of teaching hours of teachers, (6) implementation of teaching and learning program conducted after the teacher and the learners perform prayers Duha, reading and memorizing the Qur'an, (7) evaluation of the integrated curriculum is carried out each week on Friday to figure out the constraints and how to solve the constraints directly.Keywords: management,integrated curriculum, school of natural characteristic of IslamAbstrak: Tujuan penelitian ini adalah untuk mengetahui tentang pelaksanaan manajemen kurikulum sekolah alam.berciri khas Islam. Penelitian ini menggunakan metode deskriptif kualitatif dengan jenis studi kasus. Sumber data peneliti meliputi kepala sekolah, guru, siswa dan wakil kepala sekolah bagian kurikulum. Teknik pengumpulan data berupa wawancara, observasi, dokumentasi. Analisis data dilakukan bersamaan dengan pengumpulan data di lapangan dengan proses analisis terdiri dari reduksi data, display data, dan verifikasi data. Hasil penelitian ini (1) perencanaan kurikulum melalui kegiatan workshop untuk mempersiapkan perangkat pembelajaran selama satu tahun ajaran, (2) penyusunan kalender sekolah dilakukan setelah mendapat kalender pendidikan nasional, (3) penyusunan progam kerja dilakukan setiap akhir tahun ajaran baru dan sekolah melakukan evaluasi di setiap akhir tahun untuk menentukan progam kerja baru selanjutnya, (4) penyusunan jadwal pelajaran disusun oleh wakil kepala sekolah bagian kurikulum beserta tim kurikulum dengan melihat urgensi kompetensi mata pelajaran yang kemudian dikonsultasikan kepada kepala sekolah, (5) pembagian beban mengajar berdasarkan pada banyaknya guru dan jumlah jam mengajar guru, (6) pelaksanaan progam belajar mengajar dilakukan setelah guru dan peserta didik melakukan kegiatan sholat dhuha, membaca serta menghafal Al-Qur’an, (7) evaluasi kurikulum terpadu dilakukan setiap satu minggu di hari jum’at untuk mengetahui kendala dan cara menyelesaikan kendala tersebut secara langsung.Kata Kunci: manajemen, kurikulum terpadu, sekolah alam berciri khas Islam